The Effectiveness of Cultural Diplomacy in Strengthening Chernivtsi-Saskatchewan Educational Cooperation - Bohatyrets, Valentyna (Chernivtsi National University, 2022., 2022)
The triumphant cultural diplomacy has become of paramount importance in the present-day globalized world – the reality, where culture, knowledge and communication are the core constructs of technological advance and economic thriving as well as social cohesion and sustainable development. The purpose of the research is to retrospect both Canada and Ukraine’s academia and students’ input into the Canada-Ukraine Studies at Yuriy Fedkovych Chernivtsi National University. To put the topic of Ukraine-Canada cooperation into the context of cultural diplomacy, I should emphasise that our university (the then Chernivtsi State University) is a worthy example of the fact that on July 5, 1977 an action of cultural diplomacy was launched by signing an agreement (initiated by Prof. Yuriy Makar), with the University of Saskatchewan, which immensely contributed to synergy and cooperation in the educational, scientific and cultural fields. The current study on Chernivtsi-Saskatchewan Educational Cooperation found clear support for the cultural diplomacy as an efficient toolkit and best practice of building international bridges and interactions; communicated Ukraine-Canada shared values and virtues; catered to both universities/countries’ interest; offered exchange of mutually-enriched information and expertise; both parts were committed, involved, agile and open to experience of establishing and developing long-term fruitful cooperation. Importantly, Chernivtsi-Saskatchewan inter-university and Canada-Ukraine interstate cultural diplomacy act proved to be extremely successful at raising awareness of its importance, promoting understanding to provide the information that could influence its further promotion at state, local and private levels.
Вплив культурної дипломатії на зміцнення співробітництва між Чернівецьким і Саскачеванським університетами
Keywords: cultural diplomacy, Canada, Ukraine, Saskatchewan, Chernivtsi, educational cooperation, university, Canadian Studies